Expertise-Level-Dependent Functionally Plastic Changes During Motor Imagery in Basketball Players. (1st June 2018) - Zhang, Lan-Lan; Pi, Yan-Ling; Shen, Cheng; Zhu, Hua; Li, Xue-Pei; Ni, Zhen; Zhang, Jian; Wu, Yin
Highlights: Congruence in time for performing motor imagery and execution improves with the increase in motor expertise. The vividness of motor imagery is clearer in a with-ball compared to a without-ball condition. Cortical activation pattern during motor imagery is different in groups with different levels of motor expertise. Elite players showed higher brain activity in without-ball condition whereas intermediate players showed reverse pattern. Sports training history drives differences in functional neuroplasticity. Abstract: Motor imagery is the mental process of rehearsing or simulating a given action without overt movements. The aim of the present study is to examine plastic changes in relevant brain areas during motor imagery with increasing expertise level. Subjects (novices, intermediate and elite players) performed motor imagery of basketball throws under two experimental conditions (with-ball and without-ball). We found that all basketball players exhibited better temporal congruence (between motor imagery and motor execution) and higher vividness of motor imagery than novices. The vividness of motor imagery was higher for the with-ball than for the without-ball conditions in all three subject groups. The results from functional magnetic resonance imaging (fMRI) showed three different patterns of cortical activation. Activation in the left middle frontal gyrus increased and that in the left supplementary motor area decreased with increasing levels of motor expertise. Importantly, brain activation in the left postcentral gyrus was the highest in the intermediate players compared to both novices and elite players. For the elite group, these three areas showed higher activation in the without-ball condition than the with-ball condition, while the opposite trend was found in intermediate players. Our findings suggest that the level of motor expertise may be related to high-order brain functions that are linked to different activation patterns in different brain areas.